The mechanistic target of rapamycin as a regulator of metabolic function in oligodendroglia during remyelination. (April 2022) - Mather, Marie L.; Jeffries, Marisa A.; Wood, Teresa L.
Abstract: Despite evidence for prominent metabolic dysfunction within multiple sclerosis (MS) lesions, the mechanisms controlling metabolic shifts in oligodendroglia are poorly understood. The cuprizone model of demyelination and remyelination is a valuable tool for assessing metabolic insult during oligodendrocyte death and myelin degradation, closely resembling the distal oligodendrogliopathy seen in Pattern III MS lesions. In this review we discuss how metabolic processes in oligodendrocytes are disrupted in both MS and the cuprizone model, as well as the evidence for mechanistic target of rapamycin (mTOR) signaling as a key regulator of oligodendroglial metabolic function and efficient remyelination.